Profiling deaf and hard-of-hearing users of subtitles for the deaf and hard-of-hearing in Italy: a questionnaire-based study - Morettini, Agnese (MonTi Monografías de Traducción e Interpretación, 2014)
The aim of this article is to present the results of a questionnaire-based study carried out as part of the author’s Master’s Degree dissertation about Subtitles for the Deaf and Hard-of-hearing (SDH). In particular, the need to gather specific information regarding audience design will be highlighted in the paper, since this research field has long been neglected in Italy. The questions were aimed at shedding light on the needs, cultural environment and world-view of Italian SDH users, by eliciting personal data as well as subtitlerelated information. Moreover, the 232 respondents were asked to suggest improvements to SDH services in Italy. Although these first results cannot allow definite conclusions because of the limited number of respondents to the survey, they might prove to be helpful for professional translators and subtitlers to better know their intended recipients.